2003
DOI: 10.1038/sj.ijo.0802320
|View full text |Cite
|
Sign up to set email alerts
|

Night eating syndrome: effects of brief relaxation training on stress, mood, hunger, and eating patterns

Abstract: BACKGROUND: Night eating syndrome (NES) is characterized by a lack of appetite in the morning, consumption of 50% or more of daily food intake after 6:00 p.m., and difficulty falling and/or staying asleep. It has been associated with stress and with poor results at attempts to lose weight. OBJECTIVE: The purpose of this study was to determine whether a relaxation intervention (Abbreviated Progressive Muscle Relaxation Therapy, APRT) that has been shown to significantly reduce stress levels in normal, healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 19 publications
5
71
1
1
Order By: Relevance
“…Our result contradicted with the findings of the study among gynaecology and breast cancer patients underwent brachytherapy (p=0.03) (Leo´n-Pizarro et al, 2007) and among night eating syndrome (Pawlow et al, 2003). The depression score was significantly decreased by using Hospital Anxiety Depression Scale (HADS) among heart failure patients (Yu et al, 2007) and advanced cancer patients (Sloman, 2002).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our result contradicted with the findings of the study among gynaecology and breast cancer patients underwent brachytherapy (p=0.03) (Leo´n-Pizarro et al, 2007) and among night eating syndrome (Pawlow et al, 2003). The depression score was significantly decreased by using Hospital Anxiety Depression Scale (HADS) among heart failure patients (Yu et al, 2007) and advanced cancer patients (Sloman, 2002).…”
Section: Discussioncontrasting
confidence: 94%
“…On the stress level, the results supported the findings of some previous studies that investigated the impact of different relaxation technique among night eating syndrome patients (Pawlow et al, 2003), undergraduate students (Pawlow and Jones, 2002), pregnant women (Bastani et al, 2005) and healthy young adults (Emery et al, 2008). Yu et al (2007) found a medium-size effect (partial η 2 = 0.7) for alleviating psychologic distress in patients with chronic illness.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This idea is indirectly supported by the long history of unsuccessful weight loss attempts usually reported by night eaters. 32 The few available data indicate a potential beneficial effect of sertraline, 33 cognitive behavior therapy 34 and relaxation training, 35 but we still lack large randomized trials to evaluate the role of these procedures in the management of NES associated with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“…42 Subsequently, the same group reported the case of a non-obese patient with NES and depression, who underwent morning phototherapy with 10,000 lux of white light for 30 minutes; after 14 sessions, improvement of depression and symptoms of NES was observed. 43 The effect of progressive muscle relaxation therapy on stress, mood, hunger, and eating pattern was evaluated by Pawlow et al (2003) in 20 individuals with NES randomly assigned to a treatment or control group. In the latter, patients remained at rest for the same time duration of the therapy session.…”
Section: Methodsmentioning
confidence: 99%